First Record of the Genus Myopias (Hymenoptera, Formicidae) from India, with Description of New Species - Bharti, H.; Wachkoo, A.A. (Вестник зоологии, 2012)
Myopias shivalikensis Bharti et Wachkoo, sp. n. is described based on a single worker, collected in lower Shivalik range (700 m a. s. l.) of Northwest Himalaya by soil core method. The genus Myopias is recorded for the first time in India. M. shivalikensis is a cryptobiotic species with reduced body size and rudimentary eyes. It is similar to M. nops Willey et Brown, 1983, distinctly differing from all described species of this genus. Myopias shivalikensis Bharti et Wachkoo, sp. n. описан по единственному рабочему, найденному в нижней части хребта Шивалик (700 м над у. м.) в северо-западных Гималаях в почвенных пробах. Это первая находка рода Myopias в Индии. Данный вид является криптобионтом и характеризуется мелкими размерами и редуцированными глазами. Он наиболее сходен с M. nops Willey et Brown, 1983 и хорошо отличается от всех ранее описанных видов этого рода.